Malaysia : 2010 Article IV Consultation-Staff Report; Staff Statement; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for Malaysia. (IMF Staff Country Reports; Country Report, 2010)
Strong fundamentals and countercyclical policies have helped Malaysia during the global financial crisis. Executive Directors welcomed the authorities' challenge to make progress toward economic growth and structural transformation. Directors welcomed the consolidation effort in the 2010 budget, and stressed that a sound and sustained fiscal adjustment is essential. Directors appreciated the monetary policy stance to sustain noninflation growth. They welcomed the new Central Bank Act, which reinforces the underpinnings of the financial system. Directors also commended the authorities' decision to participate in the Financial Sector Assessment Program.